Sort Attack: Visualization and Gamification of Sorting Algorithm Learning - Yohannis, Alfa; Prabowo, Yulius (2015 7th International Conference on Games and Virtual Worlds for Serious Applications (VS-Games), 2015)
Algorithms are commonly perceived as a difficult subject, which is quite an irony as they have a fundamental role in computer science. Failure to master this subject will inhibit students'' capabilities as they advance to higher levels. Algorithm visualization, as an effort to overcome the problem, has been growing towards gameful visualization recently that is presumed to be able to engage learners longer and more intensely. However, integrating algorithm visualization, game elements, and instructional design is not a trivial task as it requires a careful design. Hence, a conceptual model of how algorithm learning instructions, algorithm visualization, and gamification improve learning outcomes was developed. While instructional design concerns with developing the best strategy for learning, algorithm visualization functions as a cognitive support provider and gamification works by delivering engagement. Both cognitive support and engagement moderate the learning instructions that concern with enhancing learning outcomes. Principles and elements originating from the three domains have to be taken into consideration during the designing process to produce an artifact that can deliver the essential functions of each domain. A working artifact was then constructed, as the instantiation of the model, to validate whether the idea of integrating algorithm visualization and gamification into algorithm learning instructions is capable enough to improve learning outcomes. Based on our respondents'' learning outcomes, it was found the artifact can significantly improve the procedural knowledge of learners that are indicated by their increased capability in solving sorting algorithm problems.